Pengaruh Brand Image dan Harga Terhadap Kepuasan Pelanggan Pengguna Jasa Go-Food pada Aplikasi Go-Jek: (Studi Kasus pada Warga Kelurahan Kaliabang Tengah Bekasi Utara) - Jasmine Egy Oktavia Rosita Sari; Hadita Hadita; Neng Siti Komariah (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The emergence of Go-Jek has had a positive impact on business people or entrepreneurs in Kaliabang Tengah Subdistrict, North Bekasi who operate in the culinary sector such as restaurants, shops, cafes and others. Likewise, from the consumer side of Go-Food service users in Kaliabang Tengah Subdistrict, North Bekasi who feel helped or satisfied by the Go-Food service because it allows them to choose different food menus from many restaurants or food sellers registered in the application, this service also offering efficiency and effectiveness even for those with limited time and distance. The purpose of this research is to find out whether there is an influence of Brand Image on Customer Satisfaction of Go-Food service users on the Go-Jek application and whether there is an influence of Price on Customer Satisfaction of Go-Food service users on the Go-Jek application. The research uses quantitative methods through questionnaires and data from the results of the questionnaire will be processed and tested using SPSS 27 Version. Based on the results of this research, it is concluded that Brand Image has a partial significant effect on Customer Satisfaction and Price has a partial significant effect on Customer Satisfaction.